Speculum Saxonum and Ius Municpale as Sources of Law in the Works of Tucholczyk - Bojarski, Władysław (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2019)
The paper is an English translation of Speculum Saxonum i Ius munici-pale jako źródła prawa w dziełach Tucholczyka by Władysław Bojarski, published originally in Polish in “Annales Universtitatis Nicoli Coper-nici. Prawo” in 1987. The text is published as a part of a jubilee edition of the “Adam Mickiewicz University Law Review. 100th Anniversary of the Faculty of Law and Administration” devoted to the achievements of the late Professors of the Faculty of Law and Administration of the Adam Mickiewicz University, Poznań.